Relação entre apresentação sintomatológica e desempenho motor em crianças e adolescentes diagnosticadas com transtorno do déficit de atenção/hiperatividade - Larissa Porto de Oliveira (2022)
Attention Deficit/Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder that can impact important performance areas, such as academic, social and occupational life. Children diagnosed with ADHD have motor deficits in 30 to 50% of the cases described in the literature. This study aims to investigate the relationship between the symptomatological presentation of ADHD and motor performance in children and adolescents. This is a study of secondary data, collected in the database of the Center for Investigation of Impulsivity and Attention (NITIDA). The sample consisted of 41 children and adolescents diagnosed with ADHD, mean age of 11.15 (± 1.85) years. The hypotheses of this study could not be confirmed, since the data reveal that individuals with higher inattention and hyperactivity scores did not have greater impacts on motor performance, suggesting that there is no relationship between symptomatological presentation and motor performance of children and adolescents diagnosed with ADHD, in this sample. We suggest that further studies be carried out, using a controlled sample.